Interactive mobile profiler - Lee, Nicholas Yong Hwee (2017)
Interactive Mobile Profiler is a location-based Android application that matches events created by users to other users. The target audience ranges from casual users to big event organizers. The type of users is split into two – organizers and potential participants.